Identity of Colletotrichum infections in large cardamom (Amomum subulatum Roxb.) - M R Sudharshan, A K Vijayan, J Thomas, K A Saju, T N Deka, U Gupta, A K Biswas (Journal of Spices and Aromatic Crops, 2013)
The pathogen causing blight and severe devastation of large cardamom in Sikkim and Darjeeling Hills was isolated and identified as Colletotrichum gloeosporioides (Penz.) Sacc. perfect state Glomerella cingulata (Stoneman) Spauld. & Schrenk. We propose the name, Colletotrichum blight for the disease.